Project-Based Learning to Foster Creativity and Collaboration Among High School Students - Idris, Nahri; Muis, Abd (Scientica Education Journal, 2025)
This study aims to explore how the implementation of Project-Based Learning (PjBL) can encourage the development of creativity and collaboration among high school students. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observations, and documentation of project-based learning activities in a high school. The results show that PjBL provides a space for students to express ideas creatively through real-life projects and strengthens collaborative skills such as communication, role-sharing, and shared responsibility. Furthermore, teachers play a crucial role as facilitators who guide students' exploration process. However, challenges remain in terms of time management and unequal participation among students. These findings confirm that PjBL is an effective approach in developing 21st-century skills when implemented in a structured manner and supported by the active role of teachers.